DAMPAK PERKEMBANGAN PARIWISATA TERHADAP KONDISI SOSIAL DAN EKONOMI MASYARAKAT SANUR - Made Arya Astina; Ketut Tri Budi Artani (Jurnal Ilmiah Hospitality Management, 2017)
This study aims to identify the impact of tourism development on the social and economic conditions of the coastal community of Sanur, Bali.Based on the objectives of this research, several theories, concepts and literature studies referred to in the concept of tourism, the principles of tourism development, and the concept of tourism impacts. Meanwhile, the research method used was descriptive analysis of the social and economic conditions of Sanur Beach community. Direct observation and interviews of village leaders and Sanur coastal communities were conducted to be able to assess directly the existing conditions. From the results of observations and interviews, the data were processed and displayed in the form of narration and tables. By answering problem formulation from this research, the obtained data or information could be classified into positive and negative impact to social life and economics of local community, and contribute strategy to minimize negative impact of tourism to society social and economy in Sanur Beach.